(untitled) (The Conference Hub, 2026)
The global demand for natural, low-calorie sweeteners as alternatives to sugar and synthetic additives is a major driver of innovation in the food industry. Steviol glycosides (SGs), extracted from the leaves of Stevia rebaudiana, represent a leading solution due to their high sweetness potency (200-450 times sweeter than sucrose) and negligible caloric contribution . However, their widespread adoption is contingent on overcoming technological challenges in separation and purification to ensure cost-effectiveness, sensory quality, and purity. This review synthesizes current knowledge on both conventional and novel technologies for SG isolation, including ultrasound-assisted extraction (UAE), microwave-assisted extraction (MAE), membrane processes, and chromatographic purification. It further evaluates the implications of these technological choices on the functional implementation of SGs in modern food matrices. The analysis indicates that while conventional hot water extraction remains prevalent, emerging green technologies offer significant advantages in yield, selectivity, and sustainability. The successful integration of high-purity SGs, particularly Rebaudioside A (Reb A) and next-generation glycosides like Reb D and Reb M, into products ranging from beverages to dairy, is heavily dependent on the initial extraction and refinement processes. This paper concludes by identifying key research gaps, including the need for scalable, integrated processing systems and further clinical studies on the bioactivity of purified SGs, to fully realize their potential in promoting public health through better-for-you food products.